2020
DOI: 10.1177/2049463720940341
|View full text |Cite
|
Sign up to set email alerts
|

Online paediatric chronic pain management: assessing the needs of UK adolescents and parents, using a cross-sectional survey

Abstract: Background: Adolescent chronic pain is prevalent, and interdisciplinary treatment is recommended. Although it is well known that technology is a key part of adolescents’ daily lives, there have not been any online, interdisciplinary interventions developed for adolescents with chronic pain in a UK healthcare context. Little is known about how adolescents currently use online resources to manage chronic pain, or what guidance they seek. Methods: Ninety-five participants from the community answered this mixed-me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…There is potential for encouraging peer support through use of online interventions, especially for adolescents, for whom social media is a core part of their daily lives (Ofcom, 2019). Recent research investigating the internet needs of adolescents with chronic pain and their parents has also highlighted social media as a resource that adolescents use to help with pain management (Hurley‐Wallace et al., 2020). The exact pattern of usage of popular social media platforms, such as Instagram, and how it relates to pain management in this population is unknown, although warrants investigation in future research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is potential for encouraging peer support through use of online interventions, especially for adolescents, for whom social media is a core part of their daily lives (Ofcom, 2019). Recent research investigating the internet needs of adolescents with chronic pain and their parents has also highlighted social media as a resource that adolescents use to help with pain management (Hurley‐Wallace et al., 2020). The exact pattern of usage of popular social media platforms, such as Instagram, and how it relates to pain management in this population is unknown, although warrants investigation in future research.…”
Section: Discussionmentioning
confidence: 99%
“…Thirteen tools of 53 were available to patients, with barriers including time and funding. Despite this, a survey of adolescents and parents indicated that new, accessible online pain management interventions would be welcomed (Hurley‐Wallace et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…According to the World Health Organization, young people with chronic pain should be treated as having a serious health issue that requires active management (29) using a multidisciplinary approach (1). A UK study found that multidisciplinary treatment followed by pharmacological interventions were effective strategies in managing young people's (n = 95) pain (30). Similarly, a Swedish study found that 74% of children and young people (n = 69) used analgesics to manage their pain (31).…”
Section: Introductionmentioning
confidence: 99%
“…Further, mixed-methods survey-based research has identified social media platforms, such as Instagram and YouTube, as important resources in chronic pain management for adolescents aged 16-18-years in the UK. 27 However, pain-related internet use among older adolescents with chronic pain has not been explored qualitatively. Such research can provide insights into which resources are already being used and why.…”
mentioning
confidence: 99%